Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2017)
A dataset containing 120040 species occurrences available in GBIF matching the query: { "and" : [ { "or" : [ "BasisOfRecord is Specimen", "BasisOfRecord is Human Observation" ] }, "TaxonKey is Corvus albus Statius Muller, 1776" ] } The dataset includes 120040 records from 50 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0061772-160910150852091/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences